Austrian Neutrality: Setting the Agenda - Kristine Sue Ankenman (Hochschule Wismar, Fachbereich Wirtschaft, 2006)
The complex historical environment, in which constitutional law and policy were established, has at times made it difficult for outsiders to the policy process to understand what forces are really affecting neutrality. While many of the Cold War constraints on neutrality disappeared with the fall of the Soviet Union, new ones have evolved to replace them. There is no discounting the fact that neutrality was originally considered a foreign policy tool, designed to minimize Austrian participation in future conflicts; however, it quickly evolved into much more. By 1956, it was an integral part of Austrian security and defense policy, as well as an instrument for constructing a uniquely Austrian identity removed from a "Germanic" one. In addition to having restored independence and national sovereignty, neutrality also secured domestic stability in the form of Consociational Democracy. In the hands of Austria's determined leadership, elements of consociationalism were adapted to form the Social Partnership, Corporatism, and Proporz, which created a unique form of "domestic neutrality", where conflict was to be avoided at all cost.
Keywords: Z00; N44; Z13; 330